The Stylistic Essence and the Functions of Terminological Words - Guluzro O’rinboyeva (Zien Journals, 2022)
This article discusses specific features of terms in Modern English and Uzbek which studies isomorphic and allomorphic features of terms in compared languages. It investigates characteristics of different terminology, such as, linguistic, medical, physical terminology.
Keywords: term; scientific; linguistic terminology; conventional character.